CALPHAD : calculation of phase diagrams : a comprehensive guide - Saunders, N. (Nigel); Miodownik, A. P. (A. Peter) (Pergamon materials series, 1998)
This monograph acts as a benchmark to current achievements in the field of Computer Coupling of Phase Diagrams and Thermochemistry, often called CALPHAD which is an acronym for Computer CALculation of PHAse Diagrams. It also acts as a guide to both the basic background of the subject area and the cutting edge of the topic, combining comprehensive discussions of the underlying physical principles of the CALPHAD method with detailed descriptions of their application to real complex multi-component materials.Approaches which combine both thermodynamic and kinetic models to interpret non-equilibrium phase transformations are also reviewed.